Charged black holes in AdS spaces in 4D Einstein Gauss-Bonnet gravity - Pedro G.S. Fernandes (Physics Letters B, 2020)
Recently a non-trivial 4-dimensional theory of gravity that claims to circumvent Lovelock's theorem and avoid Ostrogradsky instability was formulated in Glavan and Lin (2020) [1]. This theory, named “4D Einstein Gauss-Bonnet gravity”, presents several novel predictions for cosmology and black hole physics. In this paper, we generalize the vacuum black hole solution of Glavan & Lin to include electric charge in an anti-de Sitter space and explore some properties of this solution such as the asymptotics, properties of the horizons, the general relativity limit and thermodynamics.